"Those Infidel Greeks" (2 vols.) The Greek War of Independence through Ottoman Archival Documents - Şükrü Ilıcak, H. (Handbook of Oriental Studies. Section 1 The Near and Middle East, 2021)
The documents edited by H. Şükrü Ilıcak in Those Infidel Greeks comprise the English translations of select documents from the Ayniyat Registers on the Greek War of Independence preserved in the Ottoman State Archives. The primary importance of these documents is that they are a clear testimony of the larger imperial context in which the Greek War of Independence evolved and proved successful. The mass of information they contain is immense and allows the reader to follow on an almost day-to-day basis how an empire tried to suppress a national uprising-the first of its kind in the early nineteenth century.. Readership: All interested in the history of the Ottoman Empire, modern Greece, nation-states established in former Ottoman territories; as well as in broader subjects, such as empire, nationalism, history of warfare.